Investigating the elements of the structure of political-social ghazals in the poems of Houshang Ebtahaj and Shafiei Kadkani - ابراهیم اقبالی; حسین رسول زاده (تاریخ ادبیات, 2009)
Ghazal has always been the focus of poets. During the Constitutional period, this format was used to express political and social issues, and despite the success it achieved, it could not be popular with the public. With the emergence of "modern poetry" a transformation occurred in contemporary Iranian literature and affected the poetic formats. By combining some elements of "modern poetry", Houshang Ebtahaj and Shafi'i Kadkani were able to compose a kind of ghazal (which, while maintaining the traditional structure of ghazal, also had some features of modern poetry)-. These ghazals can be called "modern ghazals". The elements that play a major role in the construction of these sonnets are: the use of Hafez's expressive style, the symbolic nature of the ghazal both in terms of words and images, the use of nature elements, and the use of national and historical elements. In this article, these elements have been examined in the social-political ghazals of A. Sayeh and Shafi'i Kadkani.